2024
DOI: 10.1021/acscatal.4c01263
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Reductive Conjugate Alkenylation of α,β-Unsaturated Ketones and Amides via Nickel Catalysis

Mengxin Zhao,
Luoqiang Zhang,
Jianrong Steve Zhou

Abstract: Chiral nickel complexes promoted enantioselective reductive alkenylation of a range of conjugated enones, using alkenyl bromides, triflates, and tosylates. The neutral condition was compatible with sensitive groups and azaheteroaryl rings. Importantly, alkenyl groups in products can be readily converted to functionalized alkyl groups via iron-catalyzed reductive hydrofunctionalization. Some examples of asymmetric alkenylation of N-enoyl pyrroles and indoles were also included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Our group also disclosed the nickel-catalyzed enantioselective conjugate addition of aryl and alkenyl halides to 2-enones in excellent stereoselectivity (Figure a) . We found that the aryl insertion proceeded via a novel mechanism on nickel complexes, which we called “elementary 1,4-addition” .…”
Section: Introductionmentioning
confidence: 99%
“…Our group also disclosed the nickel-catalyzed enantioselective conjugate addition of aryl and alkenyl halides to 2-enones in excellent stereoselectivity (Figure a) . We found that the aryl insertion proceeded via a novel mechanism on nickel complexes, which we called “elementary 1,4-addition” .…”
Section: Introductionmentioning
confidence: 99%